Physiological Characterization Of Three National Tobacco Varieties (Nicotiana Tabacum L.) Seedlings On Biochar Media With Variations Of Soaking Treatments - Sarina, Sarina; Rahim, Iradhatullah; Suherman, Suherman; Ilmi, Nur; Zamzam, Syamsiar (Urecol Journal. Part D: Applied Sciences, 2025)
This study aims to examine the physiological characteristics of seedlings from three national tobacco varieties (Jinten, Prancak 95, and Paiton 2) grown in biochar media under varying soaking treatments. Biochar, as a planting medium, has the potential to improve seedling quality and growth by increasing water retention capacity and soil nutrient availability. Seed soaking treatments were carried out using warm water, warm water + Azotobacter, and warm water + Biohumic to stimulate seed physiology. The Research employed a factorial Randomised Block Design (RBD) with two factors: variety and type of soaking, each repeated three times. The observed physiological parameters included the number of leaves, leaf length, plant height, leaf area, leaf colour, leaf area index, and total chlorophyll content, chlorophyll a, and chlorophyll b. The results showed that the combination of tobacco variety and soaking treatment significantly affected the physiological parameters of tobacco seedlings, both in vegetative growth and internal physiological content. The Prancak-95 variety (A2), treated with warm water + Azotobacter (D2), showed the best physiological performance in terms of plant height and leaf area. Meanwhile, the Jinten variety (A3) under the same soaking treatment showed the best leaf colour quality. In addition, the Paiton-2 variety (A1) with warm water soaking (D1) had the highest chlorophyll a content, indicating high photosynthetic activity. The combination of biochar media and biological soaking treatments effectively supported optimal seedling growth, as indicated by leaf morphology and chlorophyll content. This indicates that selecting superior varieties and appropriate soaking techniques plays a crucial role in enhancing seedling physiological efficiency and ensuring the success of sustainable tobacco cultivation.